2004
DOI: 10.1038/sj.onc.1207122
|View full text |Cite
|
Sign up to set email alerts
|

Role of RUNX family members in transcriptional repression and gene silencing

Abstract: RUNX family members are DNA-binding transcription factors that regulate the expression of genes involved in cellular differentiation and cell cycle progression. The RUNX family includes three mammalian RUNX proteins (RUNX1, -2, -3) and two homologues in Drosophila. Experiments in Drosophila and mouse indicate that the RUNX proteins are required for gene silencing of engrailed and CD4, respectively. RUNX-mediated repression involves recruitment of corepressors such as mSin3A and Groucho as well as histone deace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 49 publications
2
153
0
1
Order By: Relevance
“…It has been reported that RUNX3 interacts with mSin3 and Groucho/TLE, which associate with HDACs, and SUV39H1, a histone methyltransferase, to inhibit or silence the gene transcription (Durst and Hiebert, 2004). The two binding sites for RUNX3 that we identified on Akt1 promoter are adjacent to the STAT3-binding motifs and b-catenin/ TCF-binding elements.…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that RUNX3 interacts with mSin3 and Groucho/TLE, which associate with HDACs, and SUV39H1, a histone methyltransferase, to inhibit or silence the gene transcription (Durst and Hiebert, 2004). The two binding sites for RUNX3 that we identified on Akt1 promoter are adjacent to the STAT3-binding motifs and b-catenin/ TCF-binding elements.…”
Section: Discussionmentioning
confidence: 65%
“…It should be pointed out that Runx1 seems to be a relatively weak activator of transcription, given that DNA binding of Runx1/CBF-b on its own is necessary but insufficient to exert full activation of gene transcription (Durst and Hiebert, 2004). Thus, it was proposed that Runx1 functions as an organizing protein that facilitates assembly of transcriptional activation complexes (Kurokawa and Hirai, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding regulatory regions of target genes, AML1 has been suggested to facilitate the assembly of protein complexes involved in both transcriptional activation and repression, in a cell type-specific manner Durst and Hiebert, 2004). Thus AML1 can either repress or activate the p21 WAF-1 promoter depending on cell type.…”
Section: Domain Analysis Of Tel-aml1 M Morrow Et Almentioning
confidence: 99%